Sexual Excitation and Sexual Inhibition as Predictors of Sexual Function in Women: A Cross-Sectional and Longitudinal Study. Issue 2 (17th February 2017) - Velten, Julia; Scholten, Saskia; Graham, Cynthia A.; Margraf, Jürgen
Abstract : To date, no longitudinal studies have evaluated the predictive value of the two factors of the dual control model—sexual excitation (SE) and sexual inhibition (SI)—for future sexual function. The aims of the present study were to investigate the associations between SE/SI and sexual function and estimate their predictive value for future sexual function in a sample of women. Overall, 2, 214 women participated in a web-based survey that assessed SE, SI, and sexual function as well as symptoms of depression. The one- and two-year follow-up surveys included 396 and 382 participants, respectively. Correlational analyses and hierarchical regression analyses were conducted to analyze the relationships between predictor and outcome variables. Four factors of SE (Arousability, Partner Characteristics, Sexual Power Dynamics, and Setting) and two factors of SI (Concerns about Sexual Function and Arousal Contingency), as well as symptoms of depression and partnership status, were significant predictors of concurrent and future sexual function. Several subscales of SE and SI contributed to the prediction of future sexual function above and beyond prior sexual function levels. Our study provides the first supportive evidence for the assumptions of the dual control model that propensities for low SE and high SI influence future sexual function.